Development of Android-Based Biology Learning Media Plant Tissue-App to Train High School Students' Scientific Argumentation Skills - Wahyuni*, Rindi; Norra, Bunga Ihda; Nur Khasanah, Rita Ariyana (Jurnal IPA & Pembelajaran IPA, 2024)
Student centered learning is important to be implemented to improve and develop students' critical thinking and argumentation skills, so that students become active in learning. The importance of thinking in thinking competence in order to compete in the world of technology industry and towards the era of society 5.0 so that in the future Indonesia will become a developed country and human resources can compete internationally. However, in fact, there are still many students who do not like discussion activities with presentations in front of the class. This causes students' argumentation skills to be low and need to be improved. This is influenced by one of the learning media used by teachers still using textbooks. This study aims to produce a product in the form of biology learning media based on the android plant tissue app application that is suitable for use to train high school students' scientific argumentation skills. This study is a research and development (RD) study with the ADDIE model. Data collection was carried out using a Likert scale assessment instrument which was analyzed descriptively qualitatively and quantitatively. The results of this study are the feasibility of media experts by 98% (very feasible), material experts by 74% (feasible), from Biology teachers (81%), and responses from students by 86% (very feasible). These results indicate that the developed media is suitable for use in training high school students' scientific argumentation skills on the focus of plant tissue material.